Blackened calcium‐based composite particles and their apparent kinetics features for solar thermochemical energy storage. Issue 3 (18th December 2021) - Teng, Liang; Xuan, Yimin; Liu, Xianglei; Ding, Yulong
Abstract: The calcium looping (CaL) thermochemical thermal energy storage is one of the best high‐temperature heat storage schemes for 3th concentrating solar power (CSP) photothermal power. However, the application of this technology is greatly hindered by the low solar absorption capability and the poor cyclic stability of CaCO3 /CaO‐based material. In this article, the solar absorbing capability of CaCO3 particles is enhanced by doping Mn‐Fe oxides, meanwhile, awns of setaria faberis (ASF) and microcrystalline cellulose (MCC) are used as bio‐templates to generate pores inside the particles. The pore‐making process promotes the cyclic stability and carbonation kinetic features of the composite particles simultaneously. The test results show that the proposed particles possess adequate anti‐crushing strength, high cyclic stability, high solar absorption, and high carbonation rate. In addition, the apparent carbonation kinetic features of the composite porous particles are studied with the influencing factors such as CO2 partial pressure, reaction temperature, and particle morphology taken into consideration. A kinetic equation involving these parameters is developed with the thermogravimetry data of the prepared samples. By employing this kinetic function, the carbonation reaction of the prepared particles inside the carbonator becomes predictable, which is of great significance for the design and regulation of the carbonator achieving highly stable thermal output from the CaL thermochemical heat storage system.